Amyloid pathology modulates the relationship between subsyndromal symptomatic depression and tau accumulation in non-demented older adults - Bai, Jiahe; Wei, Xiaonan; Wei, Hongchun; Tai, Yaojun; Kong, Min; Ba, Maowen; Zhang, Chunhua (Frontiers in Aging Neuroscience, 2025)
ObjectiveSubsyndromal symptomatic depression (SSD) has been increasingly implicated in the pathophysiological processes of Alzheimer’s disease (AD). However, it remains unclear whether SSD and amyloid-β (Aβ) pathology jointly contribute to tau deposition. This study aimed to investigate the interaction between SSD and Aβ status on regional tau accumulation in non-demented older adults.Materials and methodsWe analyzed data from 391 non-demented older adults in the Alzheimer’s Disease Neuroimaging Initiative (ADNI) who underwent Aβ and tau positron emission tomography (PET) scans, as well as Geriatric Depression Scale (GDS-15) assessments. Aβ positivity (Aβ+) was defined by established tracer-specific standardized uptake value ratio (SUVR) thresholds (≥1.11 for 18F-florbetapir or ≥1.08 for 18F-florbetaben). SSD was defined as a GDS-15 score of 1–5. Linear mixed-effects models were applied to assess the longitudinal effects of SSD and Aβ status on regional tau accumulation over 2 years.ResultsAt baseline, significant interactions between SSD and Aβ status were observed for regional tau SUVRs, with the Aβ+/SSD+ group exhibiting significantly higher tau levels across all Braak stages compared with the other groups. Longitudinal analyses identified a significant three-way interaction among SSD, Aβ status, and time in the Braak III/IV and Braak V/VI regions. Moreover, the Aβ+/SSD+ group demonstrated significantly faster tau accumulation compared to all other groups. The Aβ+/SSD− group also exhibited greater tau accumulation than the Aβ−/SSD− group, whereas no significant differences were observed between the Aβ− groups.ConclusionThese findings suggest that SSD is associated with greater early tau accumulation in individuals with Aβ pathology.